The illusion of choice: an exploratory study looking at the top 10 food companies in Australia and their brand connections - Vidler, Abbie-Clare; Stoneham, Melissa; Edmunds, Melinda; Sartori, Ainslie (Wiley-Blackwell Publishing Asia, 2018)
© 2018 The Authors. Objective: To identify the brands owned by each of the 10 top grossing food companies operating in Australia and visually represent them on an infographic. Methods: Desktop research was conducted to determine Australia's 10 largest food companies based on revenue. Brand ownership for each of the companies was traced through financial records and company publications. This information was then visually documented in the form of an infographic ‘food web’ to clearly illustrate company and brand ownership. Results: Fonterra, Coca-Cola Amatil, Lion, Murray Goulburn, George Weston Foods, Wilmar, Nestle, Mondelez, Parmalat and Asahi were determined as the top 10 food companies operating in Australia. The food web illustrated that brand ownership ranged from 75 (Nestle) to four (Fonterra) brands per company. Conclusions: The food web illustrates the dominance of each of these major companies within Australia and shows how their diverse brand ownership limits consumer choice. Implications for public health: This study expands on current knowledge and further defines the breadth of market influence that the top 10 food companies have within the Australian food context, and how they use their brand power to create an illusion of choice for consumers. The food web will assist in promoting transparency of brand ownership in the Australian food market, therefore allowing consumers to make an informed decision about the food they purchase, and will allow community and other organisations to make an informed decision about which companies they form partnerships with.